IMPLEMENTASI METODE STUDENT CENTERED LEARNING PADA MENULIS TEKS PIDATO KELAS VIII SMP NEGERI 1 PERCUT SEI TUAN - Dinda Nur Maulida; Hendra Kurnia Pulungan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the importance of implementing student-centered learning in teaching speech text writing. The objectives of this study were to describe: (1) the implementation process of the Student-Centered Learning method in teaching speech text writing to eighth-grade students at SMP Negeri 1 Percut Sei Tuan; and (2) the obstacles and challenges encountered during the implementation of the Student-Centered Learning method in teaching speech text writing. This study employed a descriptive qualitative method. The research subjects consisted of one Indonesian language teacher and eighth-grade students at SMP Negeri 1 Percut Sei Tuan. The data were collected through observation, interviews, questionnaires, and documentation. The research instruments included observation sheets, interview guidelines, questionnaires, and documentation. The data were analyzed through data reduction, data display, and conclusion drawing. The findings revealed that: (1) the implementation of the Student-Centered Learning method was successfully carried out through the Discovery Learning syntax, consisting of stimulation, problem identification, data collection, data processing, verification, and generalization; and (2) the obstacles and challenges encountered included difficulties in generating and developing ideas, using persuasive language, and uneven writing skills among students due to the presence of the free-rider effect during group work.